PERANCANGAN SISTEM INFORMASI PERJALANAN WISATA ALAM DAN KOMUNITAS BERBASIS WEBSITE - Hansen Junaidi; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Indonesia is a country that has a tourist attraction and is a tourist destination. Open trips are a trending vacation style, open trips are often also called combined trips. Community natural tourism or community-based nature tourism is a group or association of people who travel. The number of open trip fraud cases makes us have to be careful in looking for open trip events. The application of an open trip event information system and a website-based natural tourism community is an effort to promote trusted open trip events to tourists. This website provides information about open trip events and also community-based nature tourism in Indonesia and educational articles when traveling on open trips. All of this is provided so that the names of tourist destinations are more widely known and encourage interest in domestic tourism. This application provides information on domestic community-based natural and natural tourism trips and payments that are still manual. In developing this website using HTML, CSS, Laravel framework, Bootstrap, and for the database using MySQL.